Republic of North Macedonia : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2020)
This Selected Issues paper on the Republic of North Macedonia focuses on income convergence and integration of North Macedonia with the European Union (EU). Based on the experience of other countries, joining the EU, which North Macedonia is aspiring to, has the potential to strengthen growth prospects. The macroeconomic indicators appear aligned with other countries at the time they started EU accession negotiations. The EU accession process constitutes a fundamental anchor for institutional reform momentum. Significant efforts to improve institutional quality in new member states took place in the years prior to EU accession to comply with Copenhagen criteria on stability of institutions, guaranteeing democracy and the rule of law, the existence of a functioning market economy, and the capacity to cope with competitive pressure and market forces within the EU. The analysis presented in this paper shows further evidence of how opening of EU accession negotiations and of better quality of institutions, rule of law, and control of corruption can improve growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Accession; CR; EU Accession Negotiations; ISCR; Negotiations; North Macedonia, Republic of